2018
DOI: 10.2528/pier17111609
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Non-Invasive Temperature Monitoring Using Uwb Radar for Cancer Treatment by Hyperthermia

Abstract: Abstract-Objective:In this paper we present a study of a novel method to noninvasively monitor temperature during thermotherapy for instance in cancer treatment using M-sequence radar technology. The main objective is to investigate the temperature dependence of reflectivity in UWB radar signal in gelatine phantoms using electrically small antennas. Methods: The phantom was locally heated up, and consequently changes of signal reflectivity were observed. Results: An approximate linear relationship between temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…Among them, we consider differential temperature monitoring using UWB radar. In our previous feasibility studies, we demonstrated the possibility to detect the reflected signal changes (differences) from the heated region in human tissue-mimicking phantoms [3,4]. This approach is based on the reflected differential signal intensity from the heated region.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, we consider differential temperature monitoring using UWB radar. In our previous feasibility studies, we demonstrated the possibility to detect the reflected signal changes (differences) from the heated region in human tissue-mimicking phantoms [3,4]. This approach is based on the reflected differential signal intensity from the heated region.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays heat therapy or thermotherapy is widely used for different medical applications. Generally, thermotherapy can be divided by temperature range to three approaches: diathermia (temperature increase by 1-3 °C, can help in treating neuralgia, muscle spasms and other physiotherapy applications by increasing blood flow), hyperthermia (temperature increase by 4-8 °C, is used as support therapy in cancer treatment) and thermal ablation (temperature increase by 20-30 °C, destroys tissues, can be used instead of open surgery in oncology) [1]. Hyperthermia therapy is of great interest for more than fifty years.…”
Section: Introductionmentioning
confidence: 99%
“…This differential signal information has to be analyzed in order to estimate tissue temperature changes inside the human body. Even small changes of relative permittivity (ε) and effective conductivity (σ) can be detected by ultra-wideband (UWB) technology [1].…”
Section: Introductionmentioning
confidence: 99%
“…hyperthermia). In our previous work we presented the possibility to measure small changes caused by local heating by means of UWB Msequence radar [1]- [2]. Hyperthermia treatment is non-toxic treatment without side effects [2].…”
Section: Introductionmentioning
confidence: 99%
“…The non-invasive temperature measurement via UWB radar is based on the assumption that dielectric properties (relative permittivity and effective conductivity) of human tissues are temperature dependent [1]. The approach is based on the recording of backscattered signals UWB from the heated region.…”
Section: Introductionmentioning
confidence: 99%